Electrodes friendly with the environment for detect heavy metal (2014)
In the last centuries, heavy metals have been extracted and processed industrially; today, they are part of our food chain and their detection has generated great international interest due to adverse effects, beyond allowed amounts for humans. For many years, mercury electrodes have been used to detect heavy metals; however, due to the new regulations and its high toxicity, new alternatives for its replacement as electrode in electroanalytical techniques have been investigated. Bismuth electrodes have been positioned as an alternative to this type of activity because of its many features similar to mercury and low toxicity. This paper provides an overview of this new type of electrode, along with different parameters to consider in order to obtain better results